OBSERVATION OF ELECTRONIC RAMAN-SCATTERING IN Y2BACUO5 - Flavell, W; Egdell, R (1989)
A low energy electronic excitation between the 2B1 and 2A1 states of Cu(II) in Y2BaCuO5 gives rise to a peak at 1169 cm-1 in Raman scattering. The electronic excitation shows strong resonant enhancement as the laser exciting line moves toward the blue end of the visible spectrum. The possible scope of electronic Raman scattering in the study of mixed oxides containing Cu(II) is discussed. © 1989.